2020
DOI: 10.3389/fcell.2020.00741
|View full text |Cite
|
Sign up to set email alerts
|

m6A Reader: Epitranscriptome Target Prediction and Functional Characterization of N6-Methyladenosine (m6A) Readers

Abstract: N 6-methyladenosine (m 6 A) is the most abundant post-transcriptional modification in mRNA, and regulates critical biological functions via m 6 A reader proteins that bind to m 6 A-containing transcripts. There exist multiple m 6 A reader proteins in the human genome, but their respective binding specificity and functional relevance under different biological contexts are not yet fully understood due to the limitation of experimental approaches. An in silico study was devised to unveil the target specificity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 93 publications
0
35
0
Order By: Relevance
“…N6-methyladenosine (m6A) is an RNA post-transcriptional modification that is most abundant in mammalian mRNA (Zaccara et al, 2019). m6A methylation is mediated by several proteins, which are categorized into three types: writers are methyltransferases, including WTAP, KIAA1429, RBM15, RBM15B, and METTL3/14/16; erasers such as FTO and ALKBH5, which are the only two identified m6A demethylases; and final function executions (readers) that include HNRNPs, YTHDF1/2/3, YTHDC1/2, IGF2BP1/2/3, and EIF3A (Chen et al, 2019;Zhen et al, 2020). Increasing evidence has identified the important roles m6A modifications play in various cellular processes and in cancer progression through regulating RNA stability, mRNA splicing and translation, and microRNA processing (Gilbert et al, 2016;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) is an RNA post-transcriptional modification that is most abundant in mammalian mRNA (Zaccara et al, 2019). m6A methylation is mediated by several proteins, which are categorized into three types: writers are methyltransferases, including WTAP, KIAA1429, RBM15, RBM15B, and METTL3/14/16; erasers such as FTO and ALKBH5, which are the only two identified m6A demethylases; and final function executions (readers) that include HNRNPs, YTHDF1/2/3, YTHDC1/2, IGF2BP1/2/3, and EIF3A (Chen et al, 2019;Zhen et al, 2020). Increasing evidence has identified the important roles m6A modifications play in various cellular processes and in cancer progression through regulating RNA stability, mRNA splicing and translation, and microRNA processing (Gilbert et al, 2016;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, other post-transcriptional processes were not evaluated and remain to be investigated further. m 6 A reader proteins, including IGF2BP1/2/3, eukaryotic initiation factor 3 and YTH domain family, members 1/2/3, can bind to an m 6 A-modified motif indirectly or directly, thus affecting RNA function ( 45 ). A previous study reported that IGF2BP2 can recognize methylated SOX2 transcripts in the coding sequence regions to prevent SOX2 mRNA degradation, which contributes to the malignant behavior of CRC ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that it enhances translation efficiency unwinding RNA transcripts while bound to the ribosome [44,50]. This puts it in direct contrast with YTHDC1 which is nuclear and has roles in RNA splicing and chromatin modification [51][52][53]. YTHDC2 functions more in line with the cytoplasmic YTHDFs 1-3 which have been shown to bind m 6 A containing transcripts and enhance translational activity or mRNA decay [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%